THE MODEL OF INTEGRATED CHARACTER EDUCATION CURRICULUM MANAGEMENT AT LPTK - Haryati, Titik; Widodo, Joko; Masrukhi, Masrukhi (The Journal of Educational Development, 2016)
The main objective of this study is to find out a final model of integrated character education curriculum management (henceforth PKPKI) that is suitable to be implemented at the Educational Institution of Education personnel (henceforth LPTK). This study was designed according to Borg and Gall’s (1989) Research and Development as it was adopted by Sugiyono (2010). The research procedures basically consisted of the introductory, developmental, and evaluative phases. The data sources were informants from the PPKn study program of three institutions, i.e. UPGRIS, IVETS, and UNDARIS. Data were drawn from the respondents through interview, observation, documentary review, and focus group discussion (FGD). The validity of the data was viewed from the perspective of credibility test by means of data source, data collection technique and member check triangulation, The data were then processed using interaction analysis. The results of this study show that the final PKPKI model is feasible to be implemented at the Pancasila and Civics Education (henceforth PPKn) Study Program of LPTK-s.